Quebec Research on Work-related Musculoskeletal Disorders: Deeper Understanding for Better Prevention - Côté, Julie; Ngomo, Suzy; Stock, Susan; Messing, Karen; Vézina, Nicole; Antle, David; Delisle, Alain; Bellemare, Marie; Laberge, Marie; St-Vincent, Marie (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2013)
SummaryThis paper aimed to demonstrate the contribution of the research performed by the musculoskeletal disorders (MSD) Research Axis group of the Quebec Occupational Health and Safety Research Network towards better understanding of work-related MSD (WMSD) development and prevention. Although the group targets its work to the Quebec population, its work has significant impact around the world, placing MSD axis members and knowledge and expertise created in Quebec on the international map. Results from the contribution of members are relevant, primarily in the demonstration of the implication of physical workload as well as organizational and psychosocial work-related factors in the development of WMSDs. Also, members have demonstrated that gender, sex, social class, age and ethno-cultural groups interact in various ways with WMSD determinants. Efforts are devoted towards improving understanding of the physiological responses linked with MSDs, which could also lead to new workplace practices in rehabilitation. The group emphasizes the integration of prevention procedures from the design stage to the workplace intervention. Members have proposed research-based tools for best practices at work and also an original conceptual model as a key, novel element of a theoretical conceptualization of WMSDs. Moreover, the group focuses on improving WMSD surveillance, using multiple sources of information, providing information on newly identified health risks and developing new methods of assessing risk in order to effectively prevent disability in the working population. Finally, results from research of the MSD axis group have implications for orienting legal processes, improving legal recognition of MSDs as occupational diseases, and contributing to the evolution of legal thinking. However, much remains to be done. To that end, the group plans and encourages new initiatives for further advancement. In conclusion, the originality of the work places the group in a favourable position to address the complexity underlying WMSDs, combining expertise that enriches fundamental, clinical and population-based research.